Efektivitas Pendidikan Agama Islam dalam Membentuk Karakter Religius Pelajar SMA di Kota Tarakan: Studi Deskriptif melalui Pendekatan Literatur - Dwi Oktarosada; Fahmi Syam (Pusat Riset dan Inovasi Nasional, 2025)
Islamic Religious Education (IRE) plays a strategic role in shaping students’ religious character, especially in a modern era filled with moral and spiritual challenges. IRE is not merely about delivering theoretical religious knowledge but is more focused on instilling Islamic values into students' daily lives. This study aims to analyze the effectiveness of Islamic Religious Education in shaping the religious character of senior high school students in Tarakan City by exploring its contribution to developing students’ personalities rooted in faith, noble character, and social responsibility. This research employs a qualitative descriptive approach through literature review methods, with data collected from books, academic journals, and other relevant documents. The findings reveal that IRE plays a significant role in nurturing religious character, reflected in values such as honesty, discipline, tolerance, responsibility, worship obedience, and harmonious relationships between humans and God, fellow beings, and the environment. However, the effectiveness of IRE is influenced by both internal and external factors. Internal factors include student motivation and awareness, while external factors encompass teacher competence, curriculum design, family involvement, social environment, and the use of information technology. IRE teachers are expected not only to be knowledge transmitters but also to serve as moral and spiritual role models. A contextual and applicable curriculum is essential to address the needs of today’s learners. Furthermore, active student participation in extracurricular religious activities significantly contributes to the development of religious character. Cases of juvenile delinquency, deviant behaviors, and the lack of application of religious values outside classroom settings indicate the need for stronger and more comprehensive IRE practices. This study recommends strengthening the role of IRE teachers, developing responsive curricula aligned with contemporary needs, and enhancing collaboration between schools and families to optimize the formation of morally upright and religiously aware young generations.